A giant elasmosaurid (Sauropterygia; Plesiosauria) from Antarctica: New information on elasmosaurid body size diversity and aristonectine evolutionary scenarios - O'gorman, Jose Patricio; Santillana, Sergio Nestor; Otero, R.; Reguero, Marcelo Alfredo (Cretaceous Research)
Aristonectines show a highly derived morphology among elasmosaurid plesiosaurs, including some species with large body size. A new postcranial skeleton is described from the uppermost Maastrichtian levels of the López de Bertodano Formation, Seymour Island (= Marambio), Antarctica, being referred to as cf. Aristonectes sp; the most striking feature of the specimen described is its large body size, among the largest elasmosaurids worldwide. The occurrence of this specimen, located approximately 2.3 m or less below the Cretaceous-Paleogene (K/Pg) boundary, indicates the persistence of aristonectines at high latitudes and also it verifies their chronostratigraphical distribution until the end Cretaceous, before the mass extinction. Elasmosaurid diversity in terms of body size, possible relation of this body size, the trophic niche and abiotic drivers in aristonectine evolution are discussed. The body size inferred for MLP 89-III-3-1 seems to indicate an environment with high primary productivity, suggesting that these conditions persisted until the K/Pg mass extinction. Fil: O'gorman, Jose Patricio. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Santillana, Sergio Nestor. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Otero, R. Universidad de Chile; Chile. Consultora Paleosuchus Ltda; Chile Fil: Reguero, Marcelo Alfredo. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina